Application of Factorial Design on the Extraction of Green Tea Leaves (Camellia sinensis L.) - Eka Indra Setyawan, Abdul Rohman, Erna Prawita Setyowati, Akhmad Kharis Nugroho (Journal of Applied Pharmaceutical Science, 2018)
Green tea (Camellia sinensis L.) contains bioactive compounds such as epigallocatechin gallate (EGCG), caffeine, and gallic acid. The study aimed to optimize the extraction condition using the experimental design of factorial design. Two variables namely water temperature (75 and 95oC) and brewing number (one and two-times) were used and objected to factorial design in order to get the optimum condition. The determination of EGCC, caffeine, and gallic acid was carried out using high-performance liquid chromatography method equipped with the UV-visible detector. The result showed that the extraction yield varied from 4.48%-7.56%. The level of EGCG and caffeine in green tea extract varied from 251.96-393.34 mg/g dry weight and 32.94-46.82 mg/g dry weight, while the level of gallic acid could not be quantified in each experiment because it was below the limit of quantification (LOQ). The predicted optimum extraction condition consisted of water temperature at 95oC with two-times brewing. Using this optimum condition, the concentrations of EGCG, caffeine and the extraction yield were of 356.43 mg/g dry weight, 38.76 mg/g dry weight, and 5.76%, respectively.
Keywords: Factorial design,optimization, green tea,extraction.